ANALISIS MOTIF PERILAKU BULLYING DI SMPN 1 DUAMPANUA - Hasmi, Hasmiah (Institut Agama Islam Negeri Parepare, 2025)
Bullying is aggressive behavior that is carried out repeatedly against weak people to gain validation from peers, thus providing personal satisfaction for the perpetrator. The aim of this research is to find out what forms of bullying occur at SMP 1 Duampanua, the factors that are the motives for bullying behavior, and what the psychological impact is on the perpetrators. This type of research uses qualitative methods with a case study approach and data collection using observation and interview methods. The data sources used were 1 subject from observation results and 4 supporting subjects. Meanwhile, the data analysis techniques used are data reduction, data presentation and conclusions. The results of this research show that there are several (1) forms of bullying behavior that occur at SMPN 1 Duampanua, namely physical, verbal, psychological and cyber bullying. (2) Factors that become motives for bullying behavior are biological factors, superiority, temperament, bad prejudice and environmental factors. (2) The psychological impact caused by the perpetrator of bullying is high self-confidence, stubbornness, difficulty in controlling emotions, anxiety and stress.